SECURITY ENGINEERING FOR ONLINE DATING APPLICATION - Adi Satrya, Rehan
Online dating application are an example of social media that are commonly used today. It connects two accounts by matching the user's preferences and is determined by the user's choice by looking at the personal data displayed. The app that is the scope of this research is Ganelove. Ganelove is a team that makes an application with a similar name that is engaged in online dating specifically for students as part of the Merdeka Belajar Kampus Merdeka - Digital Innovation & Entrepreneurship (Diginove) program. It is hoped that this application can overcome the problems that occur among students from lack of socialization, lack of interaction, to finding new partners, especially during the pandemic. Some of this personal data is PII (Personally Identifiable Information). Because they store such data, online dating apps often experience security issues in the privacy sector such as fake users, data theft, man in the middle, and the problem of determining how to verify breaches that occur. To safeguard user privacy, various privacy safeguard features such as Verification, User Data Encryption, End-to-End Encryption, and Secure Network Communication are built. To handle these violations, the application also needs to handle the extraction of digital evidence if a forensic situation requires it. The result of this research is that the Secure Network Communication feature fails, the forensic support feature for detecting fake screenshots needs more exploration, and the other features successfully solve the problem as designed. However, these features still have room for improvements that can be made if this research is to be continued through further iterations in the future.